The Factor Structure of the Eating Disorder Examination in Clinical and Community Samples - Byrne, S.; Allen, K.; Lampard, Amy; Dove, E.; Fursland, A. (John Wiley & Sons, Inc., 2010)
Objective: To assess the factor structure of the Eating Disorder Examination (EDE) in three different samples and to compare the goodness-of-fit of five models of EDE data. Method: The EDE was administered to eating disordered (n = 158), treatment-seeking obese (n = 170) and non-eating disordered community-based (n = 329) participants. Confirmatory factor analysis was used to compare the validity of the original four-factor EDE model with that of three-, two-, and one-factor models. Results: None of the tested models provided a ‘‘good fit’’ to the data in any sample, with the exception of a brief one-factor model in the eating disorder group. Estimations of internal consistency, reliability, and validity were superior for the one-,two-, and three-factor models compared to the four-factor model in all samples. Discussion: Overall, there was more support for a one-factor model of EDE data than for a multi-factorial model. It may be more appropriate to use Global EDE scores than individual subscale scores for research purposes.